Reflective Teaching, Self and Coping with Negative In-school Factors - Mark Anthony Minott (Arizona State University, 2010)
The connection between reflective teaching and coping with negative in-school factors is documented in international literature. There is however no known local research in the Cayman Islands which examines these areas. This paper contributes to filling this literary gap, by reporting on a study which seeks to understand (from the perspective of local teachers) what constitute reflective teaching, negative in-school factors, and how teaching reflectively aid in coping with negative factors. In-school factors cited by teachers in the study are: heavy workload, mandated policies, disagreement with colleagues and inadequate interpersonal relational skill among colleagues. By reflecting on these factors, the respondents arrived at a number of solutions to the challenge of heavy work load and employed both direct and indirect coping strategies in response to mandated policies and inadequate interpersonal relational skills among colleagues.